Stomach Content Analysis Of Anabas Testudineus Captured In The Palm Tree Plantation Canals, Bencah Kelubi Village, Kampar Regency, Riau Province - Gustari, Rilla; ', Windarti; ', Yuliati (Jurnal Online Mahasiswa (JOM) Bidang Perikanan dan Ilmu Kelautan, 2014)
Anabas testudineus is freshwater fish that commonly inhabit streams, rivers and canals in Riau. This fish is relatively cheap protein sources for people. However, information on biological aspects of this fish is limited. To understand the stomach content analysis of this fish, a study has been conducted from January – March 2014. The fish was sampled in the irrigation canals of the palm plantation area, using fish trap and line fishing. Stomach content of the fish was analyzed to calculate the Preponderance Index (PI).Total, there were 106 fishes captured, but 31 of them had empty stomach and could not be used for stomach content analysis. The number of fish analysed was 69. Results shown that the main food of A. testudineus was phytoplankton, namely Chlorophyceae (PI 89.00%), Bacillariophyceae (PI 4.42%) and Cyanophyceae (PI 5.36%). The most common Chlorophyceae present in the stomach was Ulotrix sp (PI 87.6%). Zooplankton was rare and the there was only remains of Crustacean (PI 1.22%) present in the stomach. Based of data obtained, it can be concluded that main food of A.testudineus is phytoplankton and the fish can be categorized as plankton feeder.Keyword : Anabas testudineus, Canal, Stomach Content Analysis, Index of Preponderance